Ultrasonic monitoring of infrastructure: Comparison of conventional and laser systems - Majhi, S.; Mukherjee, Abhijit; Karaganov, V.; Uy, B. (2017)
© 2017 Taylor & Francis Group, London. Civil infrastructure require consistent assessment to maintain their integrity. Wave-based techniques can be perceived as a better scientific alternative to methods like visual inspection, vibration based techniques, etc., in identification and location of damage. Contact ultrasonic techniques like PZT systems rely greatly on the uniformity of spread of the coupling gel from the transducer to the structure and the contact pressure. Recent developments in laser ultrasonic techniques have opened up the opportunity for remote inspection of large structures on account of its non-contact nature and its ability deliver a higher magnitude of energy (˜1 Joule) in comparison to the existing methods (order of µJoule). In the present work, ultrasonic guided waves in the specimen are generated by means of conventional PZT (contact system) and an Nd-YAG Pulsed Laser (non-contact system) and the waveforms from these techniques are received using a PZT system. The experimental results signifies the higher amount of power delivery and lower rate of attenuation for laser generated ultrasound.